Insights into bone and cartilage responses to pulsed electromagnetic field stimulation: a review with quantitative comparisons - Masante, Beatrice; Gabetti, Stefano; Silva, Joao C.; Putame, Giovanni; Israel, Simone; Bignardi, Cristina; Massai, Diana (Frontiers in Bioengineering and Biotechnology, 2025)
Bone fractures and cartilage pathologies represent a heavy socioeconomic burden for the national healthcare systems worldwide. Pulsed electromagnetic field (PEMF) stimulation has become a widely recognized treatment for enhancing bone fracture healing and reducing tissue inflammation, thereby supporting bone tissue regeneration. More recently, its effectiveness in treating cartilage degeneration and osteoarthritis has also been demonstrated. However, the effects of PEMF, particularly the underlying mechanisms related to the activation of specific signaling pathways, are not yet fully known neither correlated with the specific PEMF parameters applied. As a result, standardized protocols for PEMF treatment are lacking in clinical practice, leading to empirical application of PEMF stimulation and heterogeneity in treatment protocols. For these reasons, over the past three decades, the biological effects of PEMF on bone and cartilage tissues have been extensively investigated through both in vitro and in vivo experiments. The aim of this review is to provide a detailed overview of the performed studies, focusing on the applied PEMF stimulation parameters and the induced effects on bone and cartilage tissues. Furthermore, to enable comparisons across various published protocols and to aid in understanding the correlation between applied PEMF parameters and their resulting biological effects, we propose, for the first time, a quantitative descriptor for PEMF stimulation, termed PEMF dose, which accounts for magnetic field intensity, stimulation waveform, and exposure duration. The use of this comprehensive descriptor enabled the identification of common features across different studies and, in the future, it could serve as a valuable tool for refining PEMF stimulation protocols and establishing standardized guidelines to support bone and cartilage repair.